A Review of Gallic Acid-Mediated Fenton Processes for Degrading Emerging Pollutants and Dyes - Juan Pablo Pereira Lima; Carlos Henrique Borges Tabelini; André Aguiar (Molecules, 2023)
Diverse reducing mediators have often been used to increase the degradation of emerging pollutants (EPs) and dyes through the Fenton reaction (Fe2+ + H2O2 → Fe3+ + HO● + HO−). Adding reductants can minimize the accumulation of Fe3+ in a solution, leading to accelerated Fe2+ regeneration and the enhanced generation of reactive oxygen species, such as the HO● radical. The present study consisted in reviewing the effects of gallic acid (GA), a plant-extracted reductant, on the Fenton-based oxidation of several EPs and dyes. It was verified that the pro-oxidant effect of GA was not only reported for soluble iron salts as a catalyst (homogeneous Fenton), but also iron-containing solid materials (heterogeneous Fenton). The most common molar proportion verified in the studies was catalyst:oxidant:GA equal to 1:10–20:1. This shows that the required amount of both catalyst and GA is quite low in comparison with the oxidant, which is generally H2O2. Interestingly, GA has proven to be an effective mediator at pH values well above the ideal range of 2.5–3.0 for Fenton processes. This allows treatments to be carried out at the natural pH of the wastewater. The use of plant extracts or wood barks containing GA and other reductants is suggested to make GA-mediated Fenton processes easier to apply for treating real wastewater.